Efeito da tensão média e frequência na resistência a fadiga e corrosão-fadiga de parafusos prisioneiros de aço inoxidável AISI 304 - Nery, Macclarck Pessoa (2018)
The use of bolts as an element of union has a great importance in industrial situations that need frequent assembling and disassembly. In the present study, the effect of the mean stress and frequency on the fatigue of screw bolts made from cold-formed threaded bars was evaluated. The bolts was made with austenitic stainless steel, AISI 304, and it were tested in two different environments, air and 35g/L NaCl aqueous solution. Initially, tensile testing, chemical analysis, microstructural analysis, x-ray diffraction and hardness were did by the metallurgical characterization. The fatigue tests occurred with mean stress equal to 40% and 60% of yield strength. After the tests, the appearance of the fracture surface was observed. It has been found that the fatigue limit remains unchanged with respect to the mean stress in the air tests at a higher frequency. However, air tests at low frequencies and under corrosion fatigue follow Goodman's prediction. Already, in the tests under corrosion, the higher mean stress tends to decrease the value of the stress amplitude resistant to corrosion fatigue under the conditions applied in the present study. The results were compared with the theoretical models of life expectancy in fatigue and with the results of Burguete and Patterson (1995).